Analisa Keadaan Dan Sifat Tanah - Fenty Wisnuwardhani (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2015)
In planning for a strong and sturdy building is not enough to calculate in terms of loading and concreting, but there are aspects that must be considered also is the problem of ground work on which to base the establishment of a building. Soil investigation is one part of the ground work, so that by knowing the state of the soil and the soil stiffness properties, the possibility of the symptoms caused by nature such as earthquakes, floods and others that can be resolved. To that end, soil investigation needs to be done as an initial activity of the construction process is done. Issues to be examined is to know the properties of natural land which can be used as baseline data BI housing development on the road Ylang Bengkulu. So it can determine whether the land can be used for the construction of residential land. The method used in this study consisted of pengumpuan methods of data and data processing method. Methods of data analysis will be carried out in broad outline includes soil sampling, testing soil moisture content, soil density, the limits of Atterberg, inspection and testing sieving soil density (proctor). From the research data with calculation and discussion, the results obtained in laboratory tests that the water content of the soil tested had an average moisture content of = 17.752%, specific gravity average sebesar2,64 gr / cm3, In testing the limits of Consistency Land (Atterberg Limit), the test results show the value limits Liquid (LL) = 50.537%, limit Plastis (PL) = 20.895%, and the value of Plasticity Index (IP) = 29.642% On examination sieving (gradation), the test results sieving shows the value of granules through sieve no. 200 has a percentage of 93.1%> 50%, then the land including fine-grained soil (silt / clay). In the testing phase soil density (Proctor), the test results and the graph shows the value of optimum moisture content (OMC) amounted to 22.17%, and the maximum dry density (MDD) of 1.554 g / cm3. From the results of laboratory testing above, explained that the type of soil on BI Housing Project in Jalan Kenanga Bengkulu, a type of clay soil. And based on the natural properties of the land, that the land in the area bias utilized for establishing residential buildings.